Security of energy supply with change in weather conditions and dynamic thermal limits - Jayaweera, D.; Islam, Syed (2014)
© 2014 IEEE. Aging network assets, significant variations in weather conditions, increased accommodation of intermittent distributed generation, and the network operating patterns deviate actual thermal limits of assets from deterministic thermal limits. In that context, the paper proposes a model integrated innovative approach to assess the security of energy supply in an active distribution network. The approach integrates models of dynamic thermal limits, stochastic variations in weather conditions, random outages, intermittent generation outputs, and random load fluctuations into Monte Carlo simulation and quantifies the level of insecurity. The effectiveness of the approach is demonstrated by a case study. The results suggest that costs of outages can be significantly affected by combinatorial effects of weather patterns and dynamic thermal limits. Changes in weather patterns contribute more to the costs of the outages than dynamic variations in thermal limits. Latent capacities of assets do not necessarily reduce insecurity of energy supply. The paper also argues that assets in stressed distribution networks should be modeled with dynamic thermal limits for the quantification of true impacts.